Claims handling procedures: a case study of Marsh Insurance Brokers Sdn Bhd / Haynee Mohamad - Mohamad, Haynee (Faculty of Business and Management, 2010)
Insurance claims are a direct product of the insurance protection that is purchased on behalf of a client. For that reason, the management and handling of a client’s claims is the vital test of the standard of value addition and professionalism of company service. A claim settlement is an agreement between two or more parties to settle a legal claim with payment and other terms. Claim settlements can appear in a number of legal contexts. It is important to alert that settling a claim usually also eliminates the right to make future claims about the legal matter in the future. If people are dissatisfied with the settlement, they should renegotiate, rather than accepting and resolving to pursue the matter further at a later date. One of the most ordinary forms of claim settlement involves an insurance claim. When people make claims against an insurance policy, the company reviews the claim, determines if it is covered, and offers a settlement to pay the claim. Sometimes this is a clear-cut process, as when someone with complete coverage will be fully paid by the insurance company. In other cases, people may disagree on the amount of claim and the case may end up in court.